Agricultural waste-derived biochar in microbial fuel cells towards a carbon-negative circular economy. (December 2022) - Ngoc-Dan Cao, Thanh; Mukhtar, Hussnain; Yu, Chang-Ping; Bui, Xuan-Thanh; Pan, Shu-Yuan
Abstract: Agricultural wastes from cropping activities are always available with high production yield after containing organic-rich materials that can replace the commercial carbon-made components in the Microbial fuel cell (MFC) such as electrodes or catalysts. Although many studies reviewed the application of waste derived-biochar to develop a low-cost MFC, they solely discussed different functions of biochar and future research in the practically applying of the MFC. Toward the requirements of sustainable development goals regarding waste-to-energy practices, this work firstly overviews the selection of crop residues to produce biochar through different approaches and the electrochemical performance of products in MFC. Then, the context of negative CO2 emission technologies is considered following the integration of biochar as sustainable electrode materials for MFC and bioenergy with carbon capture, storage, and utilization. Finally, the application of circular economy will be discussed along with the perspectives and prospects of recent challenges, and recommendations for the future developments of agricultural waste derived-biochar as electrodes in the MFC. This review expectantly provides insight into using agricultural waste to support the sustainable development goals via MFC to adapt simultaneously water-food-energy and waste-to-energy issues. Graphical abstract: Image 1 Highlights: Fabrication and characterization of biochars from agricultural wastes are reviewed. Performance of waste-derived biochars as electrodes in the MFC is summarized. Microbial activities and cost evaluation for biochar-based electrode are discussed. Perspectives for biochar-MFC in achieving negative CO2 emissions are provided.